Activation of neuromuscular sub-regions of supraspinatus and infraspinatus during common rehabilitative exercises. (December 2021) - Zaluski, Alexandra J.; Campbell, Jeremy; Hlasny, Magda; Nedjelski, Mason; Thompson, Tanner; Vanneste, Alex; Kim, Soo Y.
Abstract: 'Regional activation' has been identified within the supraspinatus and infraspinatus. Previous EMG studies have provided insight on the different functions of the sub-regions within the supraspinatus and infraspinatus, however, to date timing of peak EMG activation has not been investigated. To assess how theses sub-regions function during commonly prescribed rehabilitation exercises, electrodes were inserted into the supraspinatus - anterior and posterior- and infraspinatus - superior and middle - of 22 healthy participants. For each sub-region, normalized EMG data - amplitude and timing - was collected from nine rehabilitation exercises - three with an elastic band and six an exercise ball. Supraspinatus posterior and infraspinatus superior had similar activation levels between elastic band exercises, but the timing of peak activation was exercise specific. In all elastic band exercises, supraspinatus posterior activated prior to supraspinatus anterior. All ball exercises elicited low-amplitude muscle activation; dynamic ball exercises had higher peak muscle activation than their static counterparts.